2020
DOI: 10.1002/psc.3250
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the correlation of microscopy‐based and volumetry‐based measurements for resin swelling in a range of potential greener solvents for SPPS

Abstract: The degree of resin swelling in a particular solvent system is one of the critical parameters for solid-phase peptide synthesis (SPPS) and for solid-phase synthesis in general. Methods used for measuring the degree of resin swelling include microscopy-based and volumetry-based methods. This study describes and compares the use of both methods for a number of commercially available resins commonly used in SPPS, with a range of solvents, which have been identified in the literature as 'greener' than DCM, DMF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…79 The paramount importance of resin swelling is highlighted by the number of publications focused on investigating this step in green solvents, 82 despite traditional solvents (DMF, NMP and DCM) maintaining the highest swelling values overall. 83 The concept of binary mixtures was then expanded to other SPPS steps. The Pawlas and Rasmussen group proposed a twodimensional, green approach, where the first dimension involves a full SPPS and the second describes examples of onresin derivatization in neat, green solvents or in a 1 : 1 EtOAc/ MeCN mixture (i.e., selective removal of acid-labile protecting groups and on-resin cyclization).…”
Section: Green Solid-phase Peptide Synthesis (Gspps)mentioning
confidence: 99%
See 1 more Smart Citation
“…79 The paramount importance of resin swelling is highlighted by the number of publications focused on investigating this step in green solvents, 82 despite traditional solvents (DMF, NMP and DCM) maintaining the highest swelling values overall. 83 The concept of binary mixtures was then expanded to other SPPS steps. The Pawlas and Rasmussen group proposed a twodimensional, green approach, where the first dimension involves a full SPPS and the second describes examples of onresin derivatization in neat, green solvents or in a 1 : 1 EtOAc/ MeCN mixture (i.e., selective removal of acid-labile protecting groups and on-resin cyclization).…”
Section: Green Solid-phase Peptide Synthesis (Gspps)mentioning
confidence: 99%
“…79 The paramount importance of resin swelling is highlighted by the number of publications focused on investigating this step in green solvents, 82 despite traditional solvents (DMF, NMP and DCM) maintaining the highest swelling values overall. 83…”
Section: Technologies and Synthesis Modifications Toward “Greening” P...mentioning
confidence: 99%
“…The optimal solvation of the resin in SPS is essential for efficient and high-yielding reactions. , Poor swelling causes decreased access to the reaction sites within the resin for the deprotection, acylation, and displacement steps, resulting in reduced yields. We evaluated the swelling performance of the selected greener solvents and their mixtures (GVL, DMSO, and EtOAc) alongside traditional solvents (DMF and NMP) to assess their suitability for SPS.…”
Section: Results and Discussionmentioning
confidence: 99%
“…THF was chosen as a co-solvent instead of MeCN because it swells polystyrene-based SPPS resins similarly to DMF and DCM, but provided the highest yields in our solution-phase solvent screening (Entries 4 & 9-11, Table 1). 54 Since the amine nucleophile is immobilized on resin, we utilize an excess of thioimidate, Fmoc-Gly SMe -Aib-OMe (13, Scheme 2) for the reaction. We found that the typical concentration employed for amide coupling on resin (0.1 M) was sufficient to effect complete installation of the imidazolones when treated with 0.1 M 13 and 0.1 M AcOH under gentle heating conditions at 55 • C (Scheme 2).…”
Section: Results and Discussion Optimization Of Imidazolone Formationmentioning
confidence: 99%